VARIABLES OF QUANTIFYING REPUTATIONAL DAMAGES RESULTING FROM UNFAIR COMPETITION ACTIONS - Iulian MORARU (Eastern European Journal of Regional Studies, 2024)
The problem of quantifying the reputational damage resulting from unfair competition actions derives mainly from the lack of contextually established criteria. In the same sense, the lack of relevant judicial precedents amplifies the precarious state of the system of indicative benchmarks in order to assess the damage to reputation as a result of affecting the rights and legitimate interests of the victims of unfair competition actions. Foreign methodological systems for quantifying damages caused by unfair competition actions could represent points of reference for the domestic legislator in the idea of solving practical difficulties in the process of assessing damages caused by unfair competition actions. An eloquent example could be considered the French model for evaluating the economic damage resulting from actions of unfair competition, developed by notorious practitioners in the field in question. The methodological sheets are generically called „La réparation du préjudice économique. Fiches méthodologiques et glossaire - 3e édition (2024)”.